2016
DOI: 10.1111/aab.12290
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model for predicting the stage emergence of Plutella xylostellaunder field conditions

Abstract: The diamondback moth, Plutella xylostella, is a worldwide pest of brassicas, and its biology and ecology have been extensively studied over recent years. Despite the importance of mathematical models to the management of insect pests, no stochastic model has been developed to date for P. xylostella. In this context, the study aimed to develop a stochastic model capable of describing the stage emergence of P. xylostella under field conditions. The stochastic model was developed using simple nonlinear functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The use of mathematical models for pest management purposes can have some limitations and difficulties. For example, accurate predictions of an insect's life stages in the field depend on determining an appropriate date to begin the accumulation of development rates 63,17 . In the case of S. eridania , field experiments found that females usually lay their eggs on yellow nonwoven fabric attached to stakes slightly higher than the plant canopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mathematical models for pest management purposes can have some limitations and difficulties. For example, accurate predictions of an insect's life stages in the field depend on determining an appropriate date to begin the accumulation of development rates 63,17 . In the case of S. eridania , field experiments found that females usually lay their eggs on yellow nonwoven fabric attached to stakes slightly higher than the plant canopy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that these thermal thresholds vary among species, selecting a model that best describes the temperature‐dependent development rate is an important step in understanding how the species responds to variations in temperature 16 . Once the best‐fit model has been selected, insect development can be simulated under field conditions using temperature time series data 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that females of P. xylostella usually mate and oviposit in the first 24 h of life (Talekar and Shelton, 1993), the first capture in pheromone-baited trap can be used as the date to begin rate summation to apply the stochastic model proposed by Marchioro et al (2016). This model accurately estimates the larval emergence of P. xylostella under field conditions in southern Brazil and could offer a promising tool for Integrated Pest Management purposes, although it has to be tested in canola at these latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the nonlinear model predicted a decrease of up to 33.1% in the number of generations of S. cosmioides in warmer regions where temperatures often exceeded the optimum temperature required for the species' survival [54]. The application of mathematical models in pest management might encounter several limitations, including the prediction accuracy of the life stage of the insect in the field and ambiguity in selecting a suitable date to start estimating the development rates [55]. Another potential limitation is associated with the practical application of the model for different crops.…”
Section: Discussionmentioning
confidence: 99%